Yapay zeka uygulamaları - Akkuş, Pınar (Fen Bilimleri Enstitüsü, 1990)
Bu tez çalışmasında, yapay zeka araştırmalarının bir kolu olan uzman sistem geliştirilmesi üzerinde du rulmuştur. Amaç, hem tekstil endüstrisinde güncel kul lanım için uzman sistem yaratmak, hem de yapay zeka ko nusunda gelecekte yapılacak çalışmalara kaynak oluştur maktır. Uzman sistem oluşturma çalışması yapılırken konusun da deneyimli en az bir uzmana danışılmalıdır. Sistemi geliştirmek için, amaca yönelik yapay zeka teknikleri hakkında bilgi birikimi ve bu teknikler yanında dilin uygulanabileceği bir bilgisayar işletim sisteminde ça lışma yapmak gerekmektedir. Bu tez çalışmasında, 5. kuşak yapay zeka dillerin den birinin etkin uygulaması yapılmakta ve bir alanda uzman eleman yaratma çabası olumlu sonuç vermektedir. Tezin içinde, uzman sistem tekniklerinin yanısıra, çö züm için arama ve doğal-dil işlemleri için de ufak ör nekler, uzman sistem parçalarına yerleştirilmiştir. Sü renin kısalığı nedeni ile bazı sorulara uzman sistem yetersiz kalabilir. Bununla birlikte yeni sorular için geliştirilecek yöntemler uzman sisteme eklenebilir. Bu rada seçilen programlama dilinin modülerligi anlam ka zanır. Uzman sistem, beş temel veritabanı, bilgi-tabanı, çıkarsama bölümlerini içermektedir. Bu sistem, adı verilen bir kumaş ya da desen raporuna göre dokuma ma- kinasının seçimi ve makinenin taharının (çerçevelerin hareket planının) belirlenmesini sağlar. Tekelde insa nın düşünüş ve karar verme yapısında oluşturulmuştur. Sistem, yapay zeka araştırmaları için özel olarak oluşturulmuş PROLOG programlama dili ile yazılmıştır. Dilin ardışıllık, geriye-iz sürme mekanizması, liste işlemleri özellikleri, uzman sistemi oluşturmayı temel tekniklerden soyutlamış, düşünsel teknikler üzerinde durulmuştur. Bu dili kullanabilmek için, veri yapıla rı ve arama teknikleri hakkında bilgi gerekmektedir.

The introduction of smart, autonomous computers and robots will cause a fundamental restructuring of society. Virtually all current uses and applications of computers and automation in industry are direct extensions of the basic principles of the industrial revolution. Specifi cally, the use of computers and automation has replaced human who performs routine tasks. The purpose of this project is to help the future studies about application and to give basic techniques. There are some of the basic techniques. Also, it is give a view on the feasibility or practically of machine intelligence. For this discussion and in order to remain compatible with traditional term, this project will refer to a thinking program as an intelligent program. The concept of a thinking computer implies that the computer is executing a thinking program. Determining what an intelligent program is implies that one know what in telligence means. The intelligence definition is the ability to apprehend facts, propositions and relations. Computers are well-suited to performing these types of tasks. So that, a relational database can store infor mation, accept queries and represent relations. An in telligent program is one that exhibits behavior similar to human. The field of artificial intelligence (AI) is compo sed of several areas of study. Of these, here are the most common and most important areas : Searching for solution, expert systems, natural-language processing, robotics, logic. When applied to AI, the term searching refers to the search for solutions to a problem. For example, AI-based searching in a program attempts to find the shortest route between two cities or that proves a mathematical theorem. Expert systems are AI*s first commercially product. Firstly, an expert system allows to enter information about a subject into the computer. This information is sometimes called the knowledge base. Second, it allows to interrogate this knowledge base and it acts as though it were an expert on the subject, which is the reason for its name. In less than five years, rapid change is based on expert systems. They were the first truly fi nancially success full AI products. Many AI researchers, natural-language processing is the most crucial AI goal to achieve because it enables the computer to understand human language directly. There is the problem of making the contextual informa tion. As applied to robotics, AI helps a computer control motion. For such industrial robots as the ones that assemble automobiles, the problems of AI are primarily concerned with providing smooth, natural motions within a set of discrete locations. Of the few AI products of current practical impor tance are those programs that can be used to study the logical correctness of an argument by applying the stan dard rules of logic.
Artificial intelligence applications
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1990
Keywords: Bilgisayar Mühendisliği; Bilgisayar ve Kontrol; Sistem analizi; Tekstil endüstrisi; Uzman sistemler; Yapay zeka; Computer Engineering; Computer Science and Control; System analysis; Textile industry; Expert systems; Artificial intelligence